A line-broadening free real-time 31P pure shift NMR method for phosphometabolomic analysis. Issue 18 (27th August 2021) - Kaup, Karl Kristjan; Toom, Lauri; Truu, Laura; Miller, Sten; Puurand, Marju; Tepp, Kersti; Käämbre, Tuuli; Reile, Indrek
Abstract : Real-time pure shift NMR simplifies 31 P spectra of nucleotides, allowing easier spectra analysis in phosphometabolomics. Abstract : Phosphometabolomics by 31 P NMR can be challenging, since overlapping multiplets of homonuclear coupled phosphorus nuclei complicate spectral analysis. Pure shift NMR allows to simplify such spectra by collapsing multiplets into singlets, but most pure shift methods require substantially elongated measurement times or cause disturbing spectral line broadening. Herein, we combine established pure shift NMR and artefact suppression techniques to record 31 P pure shift NMR spectra without penalties in measurement time or line width. Examples are demonstrated in resolution of a mixture of nucleotide triphosphates and a biological sample of 18 O labelled ATP isotopomers.